2021
DOI: 10.4149/bll_2021_119
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of vitamin D deficiency in patients with COVID-19 pneumonia

Abstract: BACKGROUND: Vitamin D has anti-infl ammatory and immunomodulatory effects via the downregulation of pro-infl ammatory cytokines. We aimed to demonstrate the effect of vitamin D levels on survival in COVID-19 patients. MATERIALS AND METHODS: 207 COVID-19 patients were included in the study. Serum vitamin D levels were measured, and patients with levels < 20 ng/ml or 21 to 30 ng received a single 300.000 IU dose of vitamin D. RESULTS: Of 207 patients, 37 received vitamin D, while 170 did not. Demographic, radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This finding is in line with the international literature, highlighting the importance of adequate vitamin D levels for immune function, prevention of acute respiratory infections including COVID-19, and recovery [18,19,24,25].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with the international literature, highlighting the importance of adequate vitamin D levels for immune function, prevention of acute respiratory infections including COVID-19, and recovery [18,19,24,25].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, vitamin D can downregulate pro-inflammatory cytokines and balance the inflammatory response, thereby avoiding the cytokine storm-induced host tissue damage during acute viral infection ( 11 , 12 ). Despite some controversy and inconsistency ( 13 , 14 ), multiple studies have suggested that vitamin D may reduce COVID-19 mortality and severity in hospitalized patients, especially in adults with vitamin D deficiency ( 15 , 16 ). Notably, a recent study revealed an association between vitamin D deficiency and clinical severity and inflammatory markers in pediatric COVID-19 cases, and recommended preventive vitamin D supplementation ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study on COVID-19 patients who had and did not have Vit D replacements, only 1 patient (2.7%) died in the Vit D replacement group while 24 patients (14.1%) died in the non-replacement group (p=0.038). It has been reported that a single dose of 300,000 IU Vit D may be useful in the treatment of COVID-19 (20). Unlikely, another study reported that there was no link between serum Vit D concentrations and the risk of severe COVID-19 infection or death (21).…”
Section: Ilie Et Al Investigated the Relationship Of Mean Vit D Level...mentioning
confidence: 99%